2010
DOI: 10.1159/000316374
|View full text |Cite
|
Sign up to set email alerts
|

Occupational Risks and Hepatitis B Vaccination Status of Dental Auxiliaries in Nigeria

Abstract: Objective: To assess the occupational exposure to needlestick and sharps injuries and hepatitis B vaccination status among dental auxiliaries. Subjects and Methods: A descriptive cross-sectional survey of 83 dental auxiliaries was conducted that included 12 technologists, 11 therapists, 53 nurses/surgical assistants, and 7 record officers. The survey included demography, history of needlestick and sharps injury, hepatitis B vaccination, knowledge and attitude towards HIV-infected patients, and the dental auxil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 19 publications
1
19
1
Order By: Relevance
“…Azodo et al en 2010 reported a frequency of 41% of blood exposure accidents occurring in a 12-month period on a population of auxiliary dentists in Nigeria [13]. The high proportion noted in this last study is probably due to their status as auxiliary dentists.…”
Section: Frequency Of Accidents Of Exposure To Blood (Bea)mentioning
confidence: 51%
“…Azodo et al en 2010 reported a frequency of 41% of blood exposure accidents occurring in a 12-month period on a population of auxiliary dentists in Nigeria [13]. The high proportion noted in this last study is probably due to their status as auxiliary dentists.…”
Section: Frequency Of Accidents Of Exposure To Blood (Bea)mentioning
confidence: 51%
“…A study conducted with Saudi dentists showed that 94,5% of them were vaccinated against HBV, but only 48,6% knew their serological status for anti-HBs 12 . Similarly, studies with Nigerian dentists and dental assistants showed similar results 13,14 . A guideline published in February 2014 by the Swiss Federal Office of Public Health recommended that all DHCP should have at least one valid protection against hepatitis B, measles, mumps, rubella, influenza, varicella, diphtheria, tetanus, poliomyelitis, and pertussis 15 .…”
Section: Discussionmentioning
confidence: 62%
“…Compared to the general population, dentists were frequently found to experience lower rates of morbidity and mortality, mainly due to their relatively healthy lifestyle and better knowledge in disease prevention [1][2][3] . Despite that, the health of dentists should not be overlooked because it has been well recognized that various occupational and work environmental hazards could pose adverse effects to dentists, including musculoskeletal 4,5) / connective tissue 6) disorders, skin disease 7) , metabolic disorder 8) , infection [9][10][11] , gastroenterological disorder 12) , and cancer 13,14) .…”
Section: Introductionmentioning
confidence: 99%